Emotion suppression, coping strategies, dietary patterns, and BMI. (April 2021) - Herren, Olga M.; Agurs-Collins, Tanya; Dwyer, Laura A.; Perna, Frank M.; Ferrer, Rebecca
Abstract: Objective: Emotion suppression (ES) is associated with unhealthy coping strategies, such as emotional eating. Physical activity (PA) is a healthy coping strategy that may attenuate the association between emotion suppression and emotional eating (EE). This study evaluated whether: 1) ES is associated with body mass index (BMI) through EE and/or dietary patterns, 2) PA moderates these relationships, and 3) these patterns differ by race/ethnicity and gender. Methods: Adult participants (N = 1674) of the Family Life, Activity, Sun, Health, and Eating study completed modified versions of the Emotion Regulation, Eating in the Absence of Hunger, and International Physical Activity Questionnaires; a validated dietary assessment; and items on demographics, height, and weight. Results: Analyses revealed a serial mediation pathway in the full sample where greater ES was associated with higher BMI through greater EE and lower fruit and vegetable (F&V) intake (B = 0.0017, CI 95% [0.0001, 0.0042]) after controlling for age, gender, and education. Hedonic snack food (HSF) intake was not a significant mediator of the ES-BMI association. Greater PA attenuated associations of ES and EE with dietary intake and BMI. The serial pathway remained significant for non-Hispanic White women only in subgroup analyses. EE was a significant mediator among women, and PA effects were largely found among Hispanics and men. Conclusions: ES was associated with higher BMI through greater EE and lower F&V, but not HSF intake. PA attenuated these associations. Differences in patterns of coping strategies may help to explain disparities in obesity-related health behavior. Highlights: Emotion suppression was related to BMI through emotional eating and F&V intake. HSF intake was not a mediator between emotion suppression and BMI. PA moderated associations among emotion suppression, emotional eating and BMI. Coping behavior differences may underlie BMI trends by race/ethnicity and gender.